Nursing team knowledge about humanized childbirth (Research, Society and Development, 2022)
Objective: to identify the level of knowledge about humanized childbirth of nursing professionals who work in the obstetric center of a medium-sized hospital in the interior of the state of Maranhão. Methodology: cross-sectional, descriptive study with a quantitative approach, using a questionnaire that addresses sociodemographic data and nurses' knowledge about humanized childbirth, containing a total of 24 questions distributed in 3 sections: the first consisting of 8 questions that characterize the sample; the second corresponds to a scale of 12 statements consisting of True/False, in order to assess the knowledge of professionals about the humanization of childbirth and the third consisting of 4 statements of the True/False type, in order to assess the knowledge of the professionals. professionals regarding the humanization policy. Results: The sample consisted of 10 nurses and 20 nursing technicians. According to the data analysis, about 2 (6.67%) of the nurses have a postgraduate degree in obstetrics; about 20 (66.67%) of the professionals did not receive training on humanized childbirth; and only 5 (17%) of the professionals received training on humanized childbirth offered by the institution. Regarding the knowledge assessment score, the professionals performed well, 11 (37%) reached a score of 13 and 6 (20%) reached 12 points, showing relevant knowledge about humanized childbirth. Conclusion: The team demonstrated knowledge about humanized childbirth, but there is still a need for investment in continuing education, as our results suggest that professionals still have doubts about some questions about humanized childbirth.